Flight behaviours in birds : studying aerial insectivores at a local scale using 3D trajectometry - Ruaux, Geoffrey (CCSD, 2022)
Flight is a locomotion mode offering numerous advantages, and has allowed birds to undergo a dramatic evolutionary radiation. This adaption deeply influences their anatomy, their physiology, and their behaviour. This manuscript firstly describes the main physical and biological principles necessary to understand flight. Then, we make a literature review on the development of flight behaviours, and describe the methods used to study flight in birds. To allow a deeper understanding of flight behaviours, we focus on two aerial insectivores: the common swift (Apus apus) and the house martin (Delichon urbicum) which perform almost all of their behaviours in flight. We use a 3D trajectometry method at a local scale in order to describe vital behaviours in these two species, and to understand how energy economy is made and modulated by specific trade-offs. Firstly, we study how common swifts drink on the wing, and we show that they actively dissipate mechanical energy when approaching a waterbody in order to reduce their impact speed, partly through sharp turns and the use of headwind. This surprisingly costly behaviour might be the result of a trade-off between energy expenditure and safety, because approaching water at a high speed is risky. Secondly, we describe several strategies used by house martins to save energy during foraging, such as the extraction of environmental energy (thermal soaring) and the optimisation of their flight speed depending on wind speed and direction. Finally, we compare the distribution of speeds between juvenile and adult individuals, and we show that juveniles exhibit more variable flight speeds than adults, possibly because their flight behaviours are not immediately optimal after leaving the nest. These results benefit to the general understanding of flight behaviours in these species very adapted to the aerial environment. Comparative studies focusing on the same behaviour in several species exhibiting a gradient in some life history traits could allow a deeper understanding of these ...